PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN PADA TOKO WILDA COLLECTION RANTAUPRAPAT - Rostika Nasution; Zulkarnain Nasution; Meisa Nasution (Politeknik Bisnis Indonesia, 2022)
This study aims to analyze The effect of social media promotion on Facebook and word of mouth on purchasing decisions at Wilda Collection Store Rantauprapat partially and simultaneously. This study uses an associative method with a quantitative approach. The sample in this study were 96 respondents using nonprobability sampling technique with purposive sampling approach with the criteria of visitors aged 18 years and over, visiting at least once, and active users of social media. The data analysis method used is the validity and rehability test, classical assumption test, multiple regression analysis test, hypothesis test through t-test and f-test, and determination coefficient test. Tests are carried out using SPSS assistance. The results showed that promotion using social media had a significant effect on consumer purchasing decisions. subsequent results show that word of mouth has a significant effect on purchasing decisions. The more often social media marketing is done, the higher the consumer's intention to buy. Keyword: Social Media Marketing, Word of Mounth, Purchase Intention, Purchase.